(untitled) (Journal of Nuclear Technology in Applied Science, 2018)
The effect of chromium and selenium with vitamin E on progester ) and estradiol-17 (E) levels of Baladi female goats was the objective of this study as new techniques for improving the reproduc tive perfonnance of Egyptian goats. Seventy-two of mature Baladi does were used through two conditions of mild and hot climates (36 animals / season). The animals were randomly divided into three equal groups, is the control group, the 2 group was supplemented by chromium in capsules and the 3 group was intramuscularly injected twice a week with 2ml VITESELEN®, (0.5 mg selenium and 10.7 IU vitamin E, Se-E). Serum honnones levels were assessed in the three experimental goats at the estrous, pregnancy and postpartum periods. The results showed that P levels during estrous cycle and mid-pregnancy periods were significantly higher in mild climate than in hot climate while opposite trend was found during early and late pregnancy as well as postpartum period. E levels during postpartum period were significantly higher in hot climate than in mild while during estrous cycle no significant differences in E2 levels due to season. Chromium showed significant (P<0.05) increase in P levels in goats during each of estrous cycle and pregnancy periods and showed significant decrease in P levels in goats during postpartum period as com pared with control. Selenium-E significantly increased the concentration in goats during each of the luteal phase of estrous cycle, pregnancy and at 30 day postpartum periods as compared with control. The opposite trend was found at 15 and 45 days postpartum. No significant difference